Optimizing Online Delivery System to Enhance Product Marketing for PT Kopie Humble Indonesia - Putri, Kadek Cemara Sutrisna; Sariani, Ni Luh Putu; Wiradyatmika, Anak Agung Gde Alit (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research addresses PT Kopie Humble Indonesia's suboptimal use of online marketing for product marketing, stemming from a need for workforce knowledge and skills. It highlights the importance of optimizing online delivery platforms to enhance product marketing strategies. Method: Utilizing socialization, training, and mentoring, the study seeks to improve staff insights and skills in product marketing. Through surveys, interviews, and qualitative analysis, the research evaluates current practices and identifies areas for improvement. Practical Applications: The research offers valuable insights for PT Kopie Humble Indonesia and similar firms leveraging online delivery for enhanced marketing. Companies can improve marketing effectiveness and overall business performance by investing in staff training, and recruitment focused on online delivery services. Conclusion: This study emphasizes the significance of addressing suboptimal online delivery utilization. It provides actionable steps for companies to enhance their marketing strategies and underscores the importance of adapting to digital trends for sustained competitiveness.